Understanding fiber quality in field-grown shaded cotton: Nitrogen fertilization implications - Raphael, Juan P.A. [UNESP]; Echer, Fábio R.; Rosolem, Ciro A. [UNESP] (Elsevier, 2024)
Context: High nitrogen rates are important to field-grown cotton (Gossypium hirsutum L.) for recovering from stresses such as light restriction and alleviating its negative impact on yield. However, there is little information on its influence on fiber quality after shading. Objective: The objective of this study was to examine fiber quality responses to nitrogen fertilization of shaded cotton. Methods: Cotton plants were exposed to a 42 % reduction in global radiation for 16–25 days during early flowering, and fertilizer with different N rates in the Center-West (Primavera do Leste - PL and Chapadão do Sul - CS) and Southeast (Itapeva - IT) Brazil. Four N rates were used in PL and IT, and 3 N rates and an early (FM 906GLT) and a late-cycle (FM 983GLT) cotton cultivar were used in CS. Fiber quality from bolls taken from entire plots (nonportioned plants) and from the lower, middle, and upper thirds of the canopy (portioned plants) was assessed. Results: The lack of interaction in most analyses indicated shading and nitrogen effects on fiber quality as independent. Shading resulted in occasional effects on micronaire, strength, length, length uniformity, and short fiber index. Micronaire of nonportioned plants decreased in response to N inputs, wherein values at the maximum N rate were lower than those at the minimum one by 5.21 % and 7.91 % in PL and IT, respectively. Increasing N rates also decreased micronaire in all canopy portions in IT and the lower third in CS but had nonconclusive effects on other fiber properties. Fiber length and strength were generally greater in the late-maturing cultivar, which had higher micronaire readings in the lower third of the canopy and lower readings in the upper canopy compared with the early cultivar. Conclusions: In conclusion, shading during early flowering has limited and inconsistent effects on cotton fiber quality. Conversely, N fertilization leads to more predictable results, so higher N rates increase the risk of heightened immature fiber percentage. Implications: The findings of this work provide new insights into how nitrogen fertilization management affects cotton fiber quality. Future research should consider other management techniques, such as the timing of the crop termination, to avoid the occurrence of low micronaire.
Keywords: Gossypium hirsutum L.; Length; Light stress; Micronaire; Plant mapping